Conselho Municipal de Educação de Itapetininga: problematizações quanto à gestão democrática, participação e autonomia - RIBEIRO, Elidia Vicentina de Jesus (2021)
The qualitative research entitled Municipal Council of Education of Itapetininga/SP: problematizations regarding democratic management, participation and autonomy, developed by means of bibliographic and documental analysis, had as its main objective to analyze the initiatives and needs for the implementation of democratic management and the possibilities in the municipality of Itapetininga, from Sub Region 1 of the Metropolitan Region of Sorocaba from the problematizations regarding the democratic management, participation and autonomy with its respective Municipal Council of Education. To achieve the objective, the following specific objectives were defined: to analyze the historical trajectory of the Municipal Councils of Education in Brazil, from the democratic management provided for in the Federal Constitution of 1988, to discuss the experience of the Metropolitan Region of Sorocaba - Sub Region 3, between the proposition of democratic management, participation and autonomy in its Municipal Councils of Education and problematize the categories of democratic management, participation and autonomy of the Municipal Council of Education of Itapetininga, in the exercise of its management, based on the councilors' minutes and/or feedback. The methodological approach was developed through qualitative bibliographical research based on identified theses and dissertations on democratic management from the Federal Constitution of 1988 to the present day, analysis of research developed under the Geplage - Group of Studies and Research, State Policy, Planning and Management of Education on CMEs of Sub Region 3 of the RMS on socially referenced quality and studies on CME of Itapetininga from the analysis of the minutes and/or feedback of their respondents. The Municipal Council of Education of Itapetininga, scope of this research, served as the object of analysis. As for the documentary studies, 151 minutes of meetings of the Itapetininga CME were considered, from 2001 to 2020, and interviews were conducted with eight respondents, directors for the 2017-2019 terms; 2019-2021, through a pre-prepared form that were added to the documents collected from the perspective of democratic management, participation and autonomy. As for the documentary studies, 151 minutes of meetings of the CME of Itapetininga were considered, from the periods 2001 to 2020 and interviews were conducted with eight respondents, councilors of the mandates 2017-2019; 2019-2021, through a pre-designed form that joined the documents collected from the perspective of democratic management, participation and autonomy. It was observed as results of the research that the Municipal Council of Education of Itapetininga, like the CMEs of the RMS, is in the process of building its democratic management, participation and autonomy, as interdependent categories whose construction takes place in a complex process, of commitment, training, co-responsibility, involvement, representativeness and parity. The research is the result of the researcher's studies with the Postgraduate Program in Education, DCHE - Department of Human Sciences in Education at the Federal University of São Carlos, Sorocaba campus, at the Doctoral level and is part of a larger research, with the title Municipal Education Council of the Metropolitan Region of Sorocaba: between successful initiatives and adverse contexts that has been developed since 2017, by GEPLAGE, Group of Studies and Research, State Policy, Planning and Management of Education.